Nasopharyngeal Local Transcriptional Profile upon SARS-CoV-2 Omicron BA.2.2 Breakthrough Infection - Yi Zhang; Yang Zhou; Yumeng Zhang; Jiazhen Chen; Jing Wu; Peng Cui; Shiyong Wang; Yuanyuan Xu; Zhongliang Shen; Tao Xu; Yang Li; Jingwen Ai; et al. (Medicine)
Abstract. The Omicron variants have continued to cause severe acute respiratory syndrome coronavirus 2 infections. To better understand the anti-viral effects of vaccination on host-virus interactions during the outbreak of BA.2.2 Omicron, we conducted RNA-seq transcriptome analysis on nasopharyngeal swabs from COVID-19 patients in Shanghai. This study was performed on selected cases from unvaccinated, fully vaccinated, and booster groups with the same founder virus infection background. We observed predominant immune cell chemotaxis and interleukin-1 production, as well as mucosal keratinization and epidermis development, in unvaccinated patients. In contrast, fully vaccinated subjects exhibited an obvious T-cell activation in the local immune response, whereas B-cell activation was higher in booster-vaccinated cases. In conclusion, our findings suggest that full or booster vaccination provides better adaptive immunity and relieve inflammation at the nasopharyngeal site, thereby reducing the risk of cytokine storm during breakthrough infection.